(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Every university has an electronic portal for education and communication purposes, which enables teachers and students to interact in a secure environment. These tools are ideal for foreign language instruction, where students particularly benefit from personal practice. Using social media can provide an interactive environment anywhere. Teachers can improve student learning by using activities on social media platforms such as Facebook, Twitter, blogs, YouTube, Edmodo, Google Hangout, Group Me, Instagram, LinkedIn, and Snapchat. This research aims to investigate the effect of usingFacebook (FB) activities on learning English, and on the interaction between Saudi students. Also, the study will test the effectiveness of the move from a teacher-centered strategy to a student-centered one in Saudi classes. This study will follow 30 Saudi female students of age between 19-21, they enrolled in English classes in Prince Sattam Bin Abdulaziz University in level one for one semester (12 weeks). The FB questionnaire will help to collect statistical data, present the percentages of agreement or disagreement towards using FB as a supportive educational tool. The data will be analyzed based on descriptive statistics. Dogoriti et al. (2014, p.259) found that most students agreed that using FB is beneficial. Although 90 percent of the students agreed that FB is not an appropriate environment for learning, they agreed (76 percent) that FB creates a sense of community within a learning environment. Also, it is stated that 31 percent of the students preferred to watch and follow the discussion rather than participate. By conducting the proposed study, it is hoped to find similar or better findings.